Cardiac hydatid cyst: case series and review of the literature - Jingjie Wang; Xing Liu; Yierzhati Aizezi; Wenzhe Li; Jingnan Xu; Yi Wang; Xiangyou Yu (BMC Infectious Diseases)
Abstract Background Echinococcosis is a zoonotic parasitic disease prevalent in pastoral areas, mainly involving the liver and lungs, and rarely affecting the brain and heart. This article describes the diagnosis and treatment of 14 patients with cardiac encapsulated cysts, with the aim of providing insights into the clinical presentation, diagnostic challenges, therapeutic strategies, and outcomes associated with cardiac encapsulated cysts. Methods This retrospective case series included 13 patients with cardiac and/or cerebral encapsulated cysts. Results We retrospectively analyzed 14 patients diagnosed with cardiac and pericardial echinococcosis between 2012 and 2024 at our hospital. The patients’ average age was 26 years, ranging from 3 to 60 years. Echinococcal cysts were found in various cardiac locations, including the pericardium (5 patients), left ventricle (3 patients), right atrium (2 patients), and apical region of the heart (1 patient). Chest pain (6 patients) was a common symptom if the cyst was in the heart, dyspnea, or cough (3 patients) if it was in the lungs, and epilepsy (1 patient) if it was in the brain. Diagnosis of this condition necessitates the performance of both laboratory tests and imaging procedures. The latter requires the expertise of a trained professional to accurately differentiate between cardiac-encapsulated cysts and other types of cysts. All patients in our study were examined as described above. The recommended course of treatment is typically surgical removal of the cyst and administration of medications to prevent recurrence. In instances where the patient declines to surgery, it is advised that they be provided with medication and scheduled for regular follow-up appointments. In our study, data were lost for two patients. Eight patients underwent open-heart surgery, one underwent craniotomy for epilepsy, one underwent thoracentesis and drainage for pleural effusion, and one patient declined surgery. Conclusions Cardiac echinococcosis is common in pastoral populations, Surgical excision combined with pharmacological treatment is the best option for the treatment of cardiac echinococcosis.